MUET workshop for UiTM Mukah students - Rijeng, Jacqueline Susan (Universiti Teknologi MARA, Sarawak, 2017)
A Malaysian University English Test (MUET) workshop was successfully carried out on 25 February 2017 at Dewan Kuliah Judan, Mukah Campus. The main objectives of this workshop were to expose students to the current MUET syllabus and to prepare them for the upcoming MUET. During this one-day workshop, students were given tips and guidance on how to answer MUET questions pertaining to Reading, Writing, Listening and Speaking Components. The hands-on exercises, simulation videos as well as mock speaking sessions aimed to help students to prepare themselves mentally, tackle their anxiety and improve their delivery on the actual day of the examination. The invited speaker, Ms Chan Ai Nyet, a qualified MUET assessor, who came all the way from UiTM Kampus Samarahan, also shared fruitful insights and personal experiences with the students. Participating in the workshop were 50 students who planned to register for the July MUET.